Modulation accuracy of binary phase-shift keying signal broadcast after injection locking of a resonant tunneling diode microwave oscillator - Cantú, H.; Romeira, B.; Figueiredo, J.; Kelly, A.; Ironside, Charlie (2013)
Injection of a binary phase-shift keyed signal to a resonant tunneling diode (RTD)-based microwave oscillator is presented in this article. The locked signal is broadcast through a wireless communications link and also converted from optical to radio frequency domain using a RTD photodetector. Modulation accuracy is evaluated through error vector magnitude and bit error rate using computer software routines. © 2012 Wiley Periodicals, Inc.